Performance Analysis of Budget Implementation During the Covid-19 Pandemic at the Technical Implementation Unit of the Immigration Office Class I TPI Kendari - Nita Hasnita; Supriyadi Supriyadi; Abdul Razak (International Journal of Social Service and Research, 2023)
This study used to analyze the performance of budget execution during the 2020 and 2021 Covid-19 pandemics at the technical unit of Kantor Imigrasi Kelas I TPI Kendari based on Regulation of the Direktur Jenderal Perbendaharaan Number PER-4/PB/2020 concerning Technical Instructions for Assessment of Performance Implementation of Ministry/Agency Expenditure Budget Indicators.This study uses a qualitative descriptive technique. Data obtained by primary data derived from interviews and secondary data derived from 2020 and 2021 Budget Implementation Performance Indicators Report at Kantor Imigrasi Kelas I TPI Kendari. Analysis inductive uses based on the results. The results of this study indicate that Kantor Imigrasi Kelas I TPI Kendari increase in the final score of budget execution performance indicators, but there were decreased on several indicators.